Elderly Self Acceptance Based on Gender and Residence and Its Implications to the Guidance and Counseling Services - Alvi Rahmi; Daharnis Daharnis; Syahniar Syahniar (Global Econedu, 2019)
This study was conducted based on the lamentations of the old people about the existence of themselves. The old people cannot accept their changes both physical and psychological.This study aims to describe the self-acceptance of the elderly in terms of gender and place of residence. The study sample consisted of 116 elderly people, 67 elderly people who lived at home and 49 elderly people who lived in the Affectionate Home of Mother Batusangkar. The instrument used is the elderly self-acceptance questionnaire with reliability of 0.840. The results of this study are the self-acceptance of the elderly differs significantly in terms of gender and place of residence and there is an interaction between sex and residence in explaining the self-acceptance of the elderly.